2021
DOI: 10.2147/ijgm.s292140
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Cardiovascular Disease Mortality in Relation to Depression and 14 Common Risk Factors

Abstract: Background Depression has been linked to a worse prognosis of Cardiovascular disease (CVD), and these two diseases share a variety of common risk factors such as unhealthy lifestyles and chronic medical conditions. However, the potential role of these common risk factors in modulating the association between depression and CVD mortality and whether the co-occurrence of depression and a specific common risk factor has a cumulative impact on CVD mortality are still largely unknown. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Our findings about overall associations between depression and mortality risk are consistent with previous study results . A study using the 1999 National Health Interview Survey linked with mortality data through 2011 showed that, adjusting for demographic factors, anxiety or depression was associated with 61% elevated risk of mortality .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings about overall associations between depression and mortality risk are consistent with previous study results . A study using the 1999 National Health Interview Survey linked with mortality data through 2011 showed that, adjusting for demographic factors, anxiety or depression was associated with 61% elevated risk of mortality .…”
Section: Discussionsupporting
confidence: 91%
“…In 2020, an estimated 21 million US adults (8.4%) had at least 1 major depressive episode . Numerous adverse outcomes have been associated with depression, including increased cardiovascular disease (CVD) incidence and premature mortality . The onset of CVD occurs an average of 7.5 years earlier in adults with mood disorders, and people with severe mental disorders, including moderate to severe depression, die an average of 10 to 20 years earlier than the general population .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, we also observed the association of depression with all-cause mortality in subjects without cancer after E-DII score adjustment and other covariates. Depression itself increases mortality ( 62 ) and depressive victims also suffer from other comorbidities such as asthma and CVD, which could worsen the overall health status and enhance the risk of mortality ( 63 , 64 ). In addition, there were no significant interaction effects between E-DII score and depression in their association with all-cause, cancer-cause death, and CVD-cause death ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depression is one of the more common mental health disorders and has been identified as a robust risk factor for suicide (Conner et al , 2013; Kessler et al , 2003). Still, far more people with depression experience premature mortality related to cardiovascular disease than death from suicide (Jia and Li, 2021). Managing concerns about risk for suicide among participants will be essential to avoid unnecessary burden on both participants and the research team.…”
Section: Safely Conduct Researchmentioning
confidence: 99%